Konseling Pasca Face Reading Untuk Meningkatkan Self Accaptance Calon Pengantin - Azmi, Irsad Roxiyul (Jurnal Bimbingan dan Konseling Islam, 2025)
Personality is an important instrument in creating family harmony. While cases of divorce are increasing, divorce is caused by differences in personality that is not understood, so they feel unsuitable, then divorce occurs. The researcher used a qualitative research method type of case study. The study intends to find the theory of face reading, which is used as an instrument of measurement tools in counseling aimed at increasing the self-acceptance of prospective wives. Furthermore, a case study was conducted to apply the counseling concept that had been found in a real counseling setting with the counselee of a prospective wife. At this stage the data is obtained through interviews and observations from clients. In this research it was categorized as quite successful, with a percentage of 70%. The success is evidenced by changes in the attitude of the client in the form of: the client knows the personality of his partner, the client understands how to respond to his partner, the client knows the lack of partners and find solutions, clients know the potential and know how to develop it, clients find ways to become ideal families, clients rarely complain about the personality of his partner.